MANAGEMENT AUDIT AS AN INSTRUMENT TO ASSESS THE EFFECTIVENESS OF HUMAN RESOURCES FUNCTION (CASE STUDY ON THE RECTORATE OF BRAWIJAYA UNIVERSITY) - Ariantini, Ester; Widijoko, Grace (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Management audit of human resources toward the Rectorate of Brawijaya University aims to know the effectiveness of the development of human resource function, to identify the weaknesses which are found, and as a recommendation or alternative improvement to reach the effectiveness of human resource development. This research applies descriptive research method. The data sources were obtained by conducting interviews, observations, and documentation. The data analysis was implemented by comparing three basic elements of management audit, such as criteria, cause, and effect. The research problem is limited on the effectiveness assessment of the human resource function in Rectorate of Brawijaya University, which are human resource planning, labor recruitment, labor selection, orientation and placement, education and training, career planning and development, work assessment, granting of compensation and rewards, manpower protection, and termination of employment. Based on the test result, it is revealed that out of ten human resources functions, there are three functions which are ineffective, those are labor recruitment, labor selection, and education and training. Based on the weaknesses found in the human resource functions, the author gives some recommendations and alternative improvements to be used by Rectorate of Brawijaya University as the consideration and feedback for the human resource development management in the future. Â Keywords: Management Audit, Effectiveness, Human Resource Function, Criteria, Cause, Effect, Recommendation